Ophthalmological standards in ocupational medicine – comparison of the Polish and British models based on selected current examples - Stopyra, Wiktor (Klinika Oczna / Acta Ophthalmologica Polonica, 2021)
A correct vision is necessary for a good performance in many professions. Whether the job involves driving a vehicle, quality control, sorting by colour in a manufacturing plant or making critical life-or-death decisions, having good vision is usually fundamental for efficient and safe performance. That is why developing the minimum ophthalmologic criteria required of employees is crucial in almost every position. In Poland, there are no singular guidelines collected on this subject. The information is scattered among ministerial ordinances (from the Minister of Health, Minister of Internal Affairs and Administration, Minister of Infrastructure and Development and even Prime Minister) or recommendations of Occupational Medicine Centers. In contrast, in the United Kingdom, The Royal College of Ophthalmologist has developed its own ophthalmological standards for employees in many positions. This article serves as a comparison of Polish and British models in terms of current occupational ophthalmologic standards. Standards for firemen, train drivers and other rail workers and for seafarers, especially sailors, were used. The most important eye functions such as visual acuity, visual field, colour vision and binocular vision were considered. The results are collected in the tables.